MAKING THE GAD BUDGET GENDER-RESPONSIVE AT THE LOCAL GOVERNMENT LEVEL - Verceles, Nathalie Lourdes A. (Philippine Journal of Social Development; Vol 1 (2009): Philippine Journal of Social Development, 2011)
This study reviews the executive and legislative policies for the GAD budget in the Philippines and examines issues that preclude the full enforcement of the GAD budget law at the LGU level.  It explores how the practical and strategic gender needs of low-income Filipino women can be better addressed by the effective and effectual implementation of the GAD budget policy.